2021
DOI: 10.1002/adfm.202010422
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of a Piezo‐Photo‐Thermal Solar Evaporator for Simultaneous Steam and Power Generation

Abstract: Water and electricity shortages constitute a global energy crisis that cannot be ignored. The sun is an unlimited source of energy, and oceans provide abundant water and renewable energy resources. In this study, poly-(vinylidene fluoride) (PVDF)/graphene solar evaporator membranes are fabricated for simultaneous freshwater production and power generation. Graphene addition transformed the PVDF crystal from the α-phase to the piezoelectric self-assembly β-phase. The resulting membrane is used to convert the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…64,65 Furthermore, realizing vapor and electricity generation at the same time becomes an interesting research direction as researchers have demonstrated electricity production induced by evaporation, 66 steam enthalpy, 67 salinity, 68 and wave energy. 69 With more possibilities of integrating advanced functional materials and expanding design principles and strategies, the broader impact of hydrogel materials in the energy−water nexus is expected to increase in importance for years to come.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 Furthermore, realizing vapor and electricity generation at the same time becomes an interesting research direction as researchers have demonstrated electricity production induced by evaporation, 66 steam enthalpy, 67 salinity, 68 and wave energy. 69 With more possibilities of integrating advanced functional materials and expanding design principles and strategies, the broader impact of hydrogel materials in the energy−water nexus is expected to increase in importance for years to come.…”
Section: Discussionmentioning
confidence: 99%
“…Other than seawater, humid air is also a reliable water source. The sorption and releasing of water in hydrogel materials, as well as their water content, are in a highly tailorable manner, allowing higher moisture uptake capacity compared to hygroscopic salts or porous particles. , Furthermore, realizing vapor and electricity generation at the same time becomes an interesting research direction as researchers have demonstrated electricity production induced by evaporation, steam enthalpy, salinity, and wave energy . With more possibilities of integrating advanced functional materials and expanding design principles and strategies, the broader impact of hydrogel materials in the energy–water nexus is expected to increase in importance for years to come.…”
Section: Conclusion and Outlookmentioning
confidence: 99%
“…Solar-driven interfacial evaporation can induce water molecules to generate electricity while desalinating. Thus, hybrid systems combining solar desalination and electricity generation have shown the potential of solar water evaporation technology for freshwater and green energy production in recent years [ 28 , 29 , 30 , 31 , 32 ]. However, as most photothermal materials are non-renewable products currently, the development of natural alternatives has gained increasing momentum in recent years [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most pressing global issues puzzling people is insufficient access to freshwater due to the rapid population growth and increasing water pollution. Solar-driven water evaporation has been regarded as a highly promising technology to generate clean water due to the abundance and environmental friendliness of solar energy resources. Therefore, significant attention has been paid to the development of high-efficiency solar vapor generators through designing smart structures and choosing advanced materials. , Consequently, it is necessary to enhance the solar absorption and conversion and heat localization and management of photothermal materials. Over the past several years, solar steam generation has achieved major breakthroughs in improving the energy utilization efficiency, depending on managing the heat loss and improving the solar absorption and conversion. …”
Section: Introductionmentioning
confidence: 99%